Heat-conducting silicone rubber composite sheet material

By modifying zinc oxide whiskers and adding thermally conductive silicone rubber composite sheet materials with raw materials such as dimethyl silicone oil and white carbon black, the problem of mechanical properties degradation in the improvement of thermal conductivity of existing thermal polymer materials is solved, and efficient thermal management and mechanical properties are achieved.

CN119899531APending Publication Date: 2025-04-29苏州技佳橡塑有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410901997.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

While the existing thermal conductivity of the polymer materials improve the thermal conductivity, the mechanical properties of the materials have significantly decreased, making it difficult to meet the thermal management needs of high-frequency electronic devices.

Method used

The thermally conductive silicone rubber composite sheet material is used to improve the thermal conductivity and mechanical properties of the material by modifying zinc oxide whiskers and adding dimethyl silicone oil, white carbon black and other raw materials.

Benefits of technology

It effectively reduces the thermal resistance of the material, improves the thermal conductivity and mechanical properties, and solves the problem of thermal management of traditional thermal conductivity materials in high-frequency electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899531A_ABST
    Figure CN119899531A_ABST
Patent Text Reader

Abstract

The invention discloses a heat-conducting silicone rubber composite sheet material, and relates to the technical field of heat-conducting fins, the heat-conducting silicone rubber composite sheet material comprises the following raw materials by weight: 100-250 parts of a composite matrix, 50-120 parts of a corrosion-resistant filler, 100-200 parts of a heat-conducting filler, 1-3 parts of a reinforcing agent, and 30-60 parts of dimethyl silicone oil; the corrosion-resistant filler is prepared from the following raw materials in percentage by mass: 50 to 60 percent of bisphenol A cyanate ester prepolymer and 40 to 50 percent of kaolin. According to the heat-conducting silicone rubber composite sheet material, the zinc oxide whiskers are modified, hydroxyl groups on the surfaces of the zinc oxide whiskers are removed, the hydrophilicity of the zinc oxide whiskers is reduced, the tightness degree of connection between the zinc oxide whiskers and a composite matrix is increased, gaps and defects can be effectively reduced, thermal resistance is reduced, and then the interface polarization intensity, the dielectric constant and loss are reduced; by adding dimethyl silicone oil, the fluidity and viscosity of the composite sheet material can be improved, and the heat-conducting property of the cured composite sheet material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat-conducting sheets, in particular to a heat-conducting silicone rubber composite sheet material. Background Art

[0002] Electronic devices are constantly developing towards being lighter, thinner, more integrated, and more high-frequency. When they work at high frequencies, the heat generated per unit volume will increase significantly. The accumulated heat will seriously affect the operating reliability of electronic devices and become a key factor limiting the working life of electronic devices.

[0003] Although traditional metal-based thermal conductive materials have high thermal conductivity, their disadvantages are high density, difficulty in processing, and lack of elasticity. Thermal conductive polymer materials have the advantages of low density, easy processing, and variable shapes. Thermal conductive composite materials based on silicone rubber are widely used in high-power electronic devices. Thermal conductive fillers used for polymers include aluminum oxide, boron nitride, metal powders (copper powder, silver powder, etc.), and carbon-based fillers (graphite, carbon nanotubes, etc.); existing studies have shown that in order to achieve high thermal conductivity of thermal conductive polymer materials, it is usually achieved by increasing the amount of thermal conductive fillers, but this method often causes a significant decrease in the mechanical properties of the material; for this reason, the present invention provides a thermal conductive silicone rubber composite sheet material to solve the above problems. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a thermally conductive silicone rubber composite sheet material, which solves the problems mentioned in the above background technology.

[0005] To achieve the above purpose, the present invention is implemented by the following technical scheme: a thermally conductive silicone rubber composite sheet material, comprising the following raw materials in weight fractions: 100-250 parts of a composite matrix, 50-120 parts of a corrosion-resistant filler, 100-200 parts of a thermally conductive filler, 1-3 parts of a reinforcing agent, and 30-60 parts of dimethyl silicone oil; The corrosion-resistant filler comprises the following raw materials in percentage by weight: 50% to 60% of bisphenol A cyanate prepolymer and 40% to 50% of kaolin.

[0006] Preferably, the preparation method of the composite matrix is: pouring methyl vinyl silicone rubber and multi-walled carbon nanotubes into a mixer in sequence, heating to 110-130°C, slowly adding conductive carbon black, and then adding SiO2 and hydroxy silicone oil in sequence, and continuing to mix for 40-50 minutes to obtain the composite matrix.

[0007] Preferably, the weight proportions of the raw materials of the composite matrix are: methyl vinyl silicone rubber 70% to 80%, multi-walled carbon nanotubes 4% to 8%, conductive carbon black 3% to 5%, SiO2 8% to 15%, and hydroxy silicone oil 1% to 3%.

[0008] Preferably, the multi-walled carbon nanotubes have a length of 10 to 20 μm, a diameter of 4 to 6 nm, and a specific surface area of ​​500 to 700 m 2 / g, purity>98%.

[0009] Preferably, the reinforcing agent is white carbon black.

[0010] Preferably, the thermally conductive filler is modified zinc oxide whisker, and the modification method thereof is: S1. Add KH550 solution and distilled water to anhydrous ethanol under stirring, stir for 5-10 minutes, and heat to 70-75°C; S2, placing zinc oxide whiskers in anhydrous ethanol, mixing, and ultrasonically vibrating for 5 to 10 minutes; S3, slowly pour the suspension of the mixed solution in S1 into the mixed solution in S2, condense and reflux for 8 to 10 hours, filter and rinse 3 to 4 times; S4. Then place it in an oven to dry, and the modified zinc oxide whisker is obtained.

[0011] Preferably, in S3, the mass ratio of KH550 solution, anhydrous ethanol and distilled water is 2:7:1.

[0012] Preferably, the preparation method of the thermally conductive silicone rubber composite sheet material is: Step 1: weigh the raw materials according to the above weight ratio and set aside; Step 2: Place the thermal conductive filler and the composite matrix in an open mixer, mix to obtain a mixed rubber, and thin it 6 to 8 times; Step 3: Add corrosion-resistant filler and reinforcing agent, mix well and let stand for 5 to 8 hours; Step 4: Finally, add dimethyl silicone oil and continue mixing; Step 5: After the mixing is completed, vulcanization is performed to obtain a thermally conductive silicone rubber composite sheet material.

[0013] Preferably, in step five, the vulcanization temperature is 170-180° C., the pressure is 8-10 MPa, and the vulcanization time is 8-12 min.

[0014] Beneficial Effects The present invention provides a thermally conductive silicone rubber composite sheet material. Compared with the prior art, it has the following beneficial effects: (1) The thermally conductive silicone rubber composite sheet material can effectively reduce gaps and defects, reduce thermal resistance, and further reduce interfacial polarization strength, dielectric constant, and loss by modifying zinc oxide whiskers, removing surface hydroxyl groups, reducing the hydrophilicity of zinc oxide whiskers, and increasing the tightness of connection with the composite matrix. The addition of dimethyl silicone oil can not only improve the fluidity and viscosity of the composite sheet material, but also improve the thermal conductivity of the composite sheet material after curing.

[0015] (2) The thermal conductive silicone rubber composite sheet material, by adding white carbon black, can not only improve the elasticity of the composite matrix, but also its surface active hydroxyl groups can interact with silicone rubber molecules to construct a spatial network structure of white carbon black-silicone rubber-white carbon black, thereby improving the mechanical properties of the composite matrix. In addition, the active hydroxyl groups on the surface of white carbon black will form hydrogen bonds and chemical bonds with hydrogen and a small amount of hydroxyl groups on the macromolecular chains in the composite matrix, thereby improving the intermolecular forces within the composite matrix, enhancing the intermolecular forces of silicone rubber, and playing a reinforcing role. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Infrared spectra of zinc oxide whiskers and modified zinc oxide whiskers provided for a thermally conductive silicone rubber composite sheet material of the present invention; Figure 2 A thermal conductivity test provided for a thermally conductive silicone rubber composite sheet material of the present invention; Figure 3 A microscopic morphology of a composite matrix provided for a thermally conductive silicone rubber composite sheet material of the present invention; Figure 4 A SEM image of a thermally conductive silicone rubber composite sheet material provided by the present invention; Figure 5 A relative dielectric constant test provided for a thermally conductive silicone rubber composite sheet material of the present invention; Figure 6 A loss factor test provided for a thermally conductive silicone rubber composite sheet material of the present invention; Figure 7 A cross-sectional microscopic morphology diagram of a thermally conductive silicone rubber composite sheet material provided by the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Example 1 A thermally conductive silicone rubber composite sheet material, the preparation method of the thermally conductive silicone rubber composite sheet material is as follows: Step 1, weigh the raw materials according to the above weight ratio: 100g of composite matrix, 120g of corrosion-resistant filler, 200g of modified zinc oxide whisker, 3g of white carbon black, and 60g of dimethyl silicone oil, and set aside; The corrosion-resistant filler includes 50% bisphenol A cyanate prepolymer and 50% kaolin; The preparation method of the composite matrix is ​​as follows: 70% of methyl vinyl silicone rubber and 8% of multi-walled carbon nanotubes are sequentially poured into a mixer, wherein the multi-walled carbon nanotubes have a length of 10 μm, a diameter of 4 nm, and a specific surface area of ​​500 m 2 / g, purity is 99%, heat to 110℃, slowly add 5% conductive carbon black, then add 15% SiO2 and 2% hydroxy silicone oil in sequence, continue mixing for 40min, and get the composite matrix; The modification method of the modified zinc oxide whisker is as follows: under stirring conditions, KH550 solution and distilled water are added to anhydrous ethanol, stirred for 5 minutes, and heated to 70°C to obtain a mixed solution 1; then the zinc oxide whisker is placed in anhydrous ethanol, mixed, and ultrasonically vibrated for 5 minutes to obtain a mixed solution 2; then the suspension of the mixed solution 1 is slowly poured into the mixed solution 2, and after condensation and reflux reaction for 8 hours, it is filtered and rinsed 3 times; finally, it is placed in an oven to dry, and the modified zinc oxide whisker is obtained; wherein the mass ratio of the KH550 solution, anhydrous ethanol and distilled water is 2:7:1, and the mass ratio of the zinc oxide whisker to anhydrous ethanol is 1:3; Step 2, placing the modified zinc oxide whisker and the composite matrix in an open mixer, mixing to obtain a mixed rubber, and thinning the mixture 6 times; Step 3, adding bisphenol A cyanate prepolymer, kaolin and white carbon black, mixing and mixing, and then standing for 5 hours; Step 4: Finally, add dimethyl silicone oil and continue mixing; Step 5: After the mixing is completed, vulcanization is performed, wherein the vulcanization temperature is 170° C., the pressure is 8 MPa, and the vulcanization time is 8 min, thereby obtaining a thermally conductive silicone rubber composite sheet material.

[0019] Example 2 A thermally conductive silicone rubber composite sheet material, the preparation method of the thermally conductive silicone rubber composite sheet material is as follows: Step 1, weigh the raw materials according to the above weight ratio: 150g of composite matrix, 85g of corrosion-resistant filler, 1500g of modified zinc oxide whisker, 2g of white carbon black, and 45g of dimethyl silicone oil, and set aside; Among them, the corrosion-resistant filler includes 55% bisphenol A cyanate prepolymer and 45% kaolin; The preparation method of the composite matrix is ​​as follows: 75% of methyl vinyl silicone rubber and 6% of multi-walled carbon nanotubes are sequentially poured into a mixer, wherein the multi-walled carbon nanotubes have a length of 15 μm, a diameter of 5 nm, and a specific surface area of ​​600 m 2 / g, purity is 98%, heat to 120℃, slowly add 4% conductive carbon black, then add 12% SiO2 and 3% hydroxy silicone oil in sequence, continue mixing for 45min, and get the composite matrix; The modification method of the modified zinc oxide whisker is as follows: under stirring conditions, KH550 solution and distilled water are added to anhydrous ethanol, stirred for 8 minutes, and heated to 75°C to obtain a mixed solution 1; then the zinc oxide whisker is placed in anhydrous ethanol, mixed, and ultrasonically vibrated for 8 minutes to obtain a mixed solution 2; then the suspension of the mixed solution 1 is slowly poured into the mixed solution 2, and after condensation and reflux reaction for 9 hours, it is filtered and rinsed 4 times; finally, it is placed in an oven to dry to obtain the modified zinc oxide whisker; wherein the mass ratio of the KH550 solution, anhydrous ethanol and distilled water is 2:7:1, and the mass ratio of the zinc oxide whisker to anhydrous ethanol is 1:3.5; Step 2, placing the modified zinc oxide whisker and the composite matrix in an open mixer, mixing to obtain a mixed rubber, and thinning through 7 times; Step 3, adding bisphenol A cyanate prepolymer, kaolin and white carbon black, mixing and mixing, and then standing for 6 hours; Step 4: Finally, add dimethyl silicone oil and continue mixing; Step 5: After the mixing is completed, vulcanization is performed, wherein the vulcanization temperature is 175° C., the pressure is 9 MPa, and the vulcanization time is 10 min, thereby obtaining a thermally conductive silicone rubber composite sheet material.

[0020] Example 3 A thermally conductive silicone rubber composite sheet material, the preparation method of the thermally conductive silicone rubber composite sheet material is as follows: Step 1, weigh the raw materials according to the above weight ratio: 250g of composite matrix, 50g of corrosion-resistant filler, 100g of modified zinc oxide whisker, 1g of white carbon black, and 30g of dimethyl silicone oil, and set aside; The corrosion-resistant filler includes 60% bisphenol A cyanate prepolymer and 40% kaolin; The preparation method of the composite matrix is ​​as follows: 80% of methyl vinyl silicone rubber and 4% of multi-walled carbon nanotubes are sequentially poured into a mixer, wherein the multi-walled carbon nanotubes have a length of 20 μm, a diameter of 6 nm, and a specific surface area of ​​700 m 2 / g, purity is 99%, heat to 130℃, slowly add 3% conductive carbon black, then add 10% SiO2 and 3% hydroxy silicone oil in sequence, continue mixing for 50min, and get the composite matrix; The modification method of the modified zinc oxide whisker is as follows: under stirring conditions, KH550 solution and distilled water are added to anhydrous ethanol, stirred for 10 minutes, and heated to 75°C to obtain a mixed solution 1; then the zinc oxide whisker is placed in anhydrous ethanol, mixed, and ultrasonically vibrated for 10 minutes to obtain a mixed solution 2; then the suspension of the mixed solution 1 is slowly poured into the mixed solution 2, condensed and refluxed for 10 hours, filtered and rinsed 4 times; finally, it is placed in an oven for drying to obtain the modified zinc oxide whisker; wherein the mass ratio of the KH550 solution, anhydrous ethanol and distilled water is 2:7:1, and the mass ratio of the zinc oxide whisker to anhydrous ethanol is 1:4; Step 2, placing the modified zinc oxide whisker and the composite matrix in an open mixer, mixing to obtain a mixed rubber, and thinning the mixture 8 times; Step 3, adding bisphenol A cyanate prepolymer, kaolin and white carbon black, mixing and mixing, and then standing for 8 hours; Step 4: Finally, add dimethyl silicone oil and continue mixing; Step 5: After the mixing is completed, vulcanization is performed, wherein the vulcanization temperature is 180° C., the pressure is 10 MPa, and the vulcanization time is 12 min, thereby obtaining a thermally conductive silicone rubber composite sheet material.

[0021] Comparative Example 1 A thermally conductive silicone rubber composite sheet material, the preparation method of the thermally conductive silicone rubber composite sheet material is as follows: Step 1: weigh the raw materials according to the above weight ratio: 100g of composite matrix, 120g of corrosion-resistant filler, and 200g of zinc oxide whisker, and set aside; The corrosion-resistant filler includes 50% bisphenol A cyanate prepolymer and 50% kaolin; The preparation method of the composite matrix is ​​as follows: 70% of methyl vinyl silicone rubber and 8% of multi-walled carbon nanotubes are sequentially poured into a mixer, wherein the multi-walled carbon nanotubes have a length of 10 μm, a diameter of 4 nm, and a specific surface area of ​​500 m 2 / g, purity is 99%, heat to 110℃, slowly add 5% conductive carbon black, then add 15% SiO2 and 2% hydroxy silicone oil in sequence, continue mixing for 40min, and get the composite matrix; Step 2, placing the zinc oxide whisker and the composite matrix in an open mixer, mixing to obtain a mixed rubber, and thinning through 6 times; Step 3, adding bisphenol A cyanate prepolymer and kaolin, mixing and mixing, and then standing for 5 hours; Step 5: After the mixing is completed, vulcanization is performed, wherein the vulcanization temperature is 170° C., the pressure is 8 MPa, and the vulcanization time is 8 min, thereby obtaining a thermally conductive silicone rubber composite sheet material.

[0022] Depend on Figure 1 It can be seen that the modified zinc oxide whiskers are between 3300 and 3750 cm -1 The intensity of the internal absorption peak increases. The main vibrations of this section are hydroxyl and amino groups. Since the original zinc oxide whiskers have hydroxyl groups, the modified zinc oxide whiskers have a certain absorption intensity in this section. KH550 contains amino groups, and the absorption peak intensity of the modified zinc oxide whiskers in this section becomes stronger, indicating that the surface of the zinc oxide whiskers modified by KH550 has amino groups. The modified zinc oxide whiskers have a strong absorption peak intensity of 1000~1200cm -1 A smaller absorption peak appears in the section, which is caused by the stretching vibration of silicon-oxygen bonds. In summary, the KH550 modification of zinc oxide whiskers is successful.

[0023] Thermal conductivity test: The sample was placed in a hot air aging box and subjected to thermal oxidation aging at 200°C. The thermal conductivity of the composite material was tested using a thermal conductivity measuring instrument produced by Xi'an Xiaxi Electronic Technology Co., Ltd. (model TC3000). The sample size was 40mm × 30mm × 5mm. The results are shown in Table 1. Figure 2 shown.

[0024] Elongation at break test: According to the GB / T 528-2009 test method, the sample was placed on a universal testing machine for measurement. The sample size was 110 mm × 8 mm × 2 mm and was dumbbell-shaped. The tensile rate was 200 mm / min. The results are shown in Table 1.

[0025] Table 1 Corrosion resistance test: The corrosive medium is a mixed aqueous solution of sodium sulfate and potassium sulfate with a molar ratio of 7:3 and a total concentration of 2 mol / L. It is dropped onto the surface of the sample and completely covered. After the surface is left to dry, it is used for corrosion test. The corrosion test is carried out in a resistance furnace at 400°C for 4 hours. Then the cross-sectional micromorphology of the sample is scanned. The results are as follows: Figure 7 As shown, spherical particles after the sample is cured and the circular holes left after they fall off can be seen. The spherical particles are cyanate ester particles dispersed in the composite matrix. At the same time, the cross-sectional morphology of the sample is relatively smooth without obvious defects. Compared with Comparative Example 1, in the present technical solution, the cross-sectional morphology of the sample after curing is relatively rough, a large number of particles are dispersed in the composite matrix, the interface between the particles and the composite matrix is ​​well bonded, and there are no obvious defects.

[0026] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0027] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0028] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A thermally conductive silicone rubber composite sheet material, characterized in that: The invention comprises the following raw materials in weight fractions: 100 to 250 parts of a composite matrix, 50 to 120 parts of a corrosion-resistant filler, 100 to 200 parts of a thermally conductive filler, 1 to 3 parts of a reinforcing agent, and 30 to 60 parts of dimethyl silicone oil; The corrosion-resistant filler comprises the following raw materials in percentage by weight: 50% to 60% of bisphenol A cyanate prepolymer and 40% to 50% of kaolin.

2. The thermally conductive silicone rubber composite sheet material according to claim 1, characterized in that: The preparation method of the composite matrix is ​​as follows: methyl vinyl silicone rubber and multi-walled carbon nanotubes are sequentially poured into a mixer, the temperature is raised to 110-130° C., conductive carbon black is slowly added, SiO2 and hydroxy silicone oil are sequentially added, and mixing is continued for 40-50 minutes to obtain the composite matrix.

3. The thermally conductive silicone rubber composite sheet material according to claim 2, characterized in that: in, The weight proportions of the raw materials of the composite matrix are: methyl vinyl silicone rubber 70% to 80%, multi-walled carbon nanotubes 4% to 8%, conductive carbon black 3% to 5%, SiO2 8% to 15%, and hydroxy silicone oil 1% to 3%.

4. The thermally conductive silicone rubber composite sheet material according to claim 1, characterized in that: The multi-walled carbon nanotubes have a length of 10 to 20 μm, a diameter of 4 to 6 nm, and a specific surface area of ​​500 to 700 m 2 / g, purity>98%.

5. The thermally conductive silicone rubber composite sheet material according to claim 1, characterized in that: The reinforcing agent is white carbon black.

6. The thermally conductive silicone rubber composite sheet material according to claim 1, characterized in that: The thermal conductive filler is a modified zinc oxide whisker, and the modification method thereof is as follows: S1. Add KH550 solution and distilled water to anhydrous ethanol under stirring, stir for 5-10 minutes, and heat to 70-75°C; S2, placing zinc oxide whiskers in anhydrous ethanol, mixing, and ultrasonically vibrating for 5 to 10 minutes; S3, slowly pour the suspension of the mixed solution in S1 into the mixed solution in S2, condense and reflux for 8 to 10 hours, filter and rinse 3 to 4 times; S4. Then place it in an oven to dry, and the modified zinc oxide whisker is obtained.

7. The thermally conductive silicone rubber composite sheet material according to claim 6, characterized in that: In S3, the mass ratio of KH550 solution, anhydrous ethanol and distilled water is 2:7:

1.

8. The thermally conductive silicone rubber composite sheet material according to claim 1, characterized in that: The preparation method of the thermal conductive silicone rubber composite sheet material is as follows: Step 1: weigh the raw materials according to the above weight ratio and set aside; Step 2: Place the thermal conductive filler and the composite matrix in an open mixer, mix to obtain a mixed rubber, and thin it 6 to 8 times; Step 3: Add corrosion-resistant filler and reinforcing agent, mix well and let stand for 5 to 8 hours; Step 4: Finally, add dimethyl silicone oil and continue mixing; Step 5: After the mixing is completed, vulcanization is performed to obtain a thermally conductive silicone rubber composite sheet material.

9. The thermally conductive silicone rubber composite sheet material according to claim 8, characterized in that: In the step 5, the vulcanization temperature is 170-180° C., the pressure is 8-10 MPa, and the vulcanization time is 8-12 min.